PERAN KAJIAN PUSTAKA DALAM MENINGKATKAN EFEKTIVITAS PENEGAKAN HUKUM ADMINISTRATIF, PERDATA, DAN PIDANA - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study discusses the role of literature review in improving the effectiveness of administrative, civil, and criminal law enforcement in Indonesia. Using a literature review method, this study analyses various primary and secondary literature related to the theory, principles, and practice of law enforcement in these three areas. The results of the study indicate that literature review is capable of identifying and evaluating weaknesses and inconsistencies in regulations, strengthening conceptual foundations, and providing evidence-based recommendations for legal system reform. Additionally, literature review enriches understanding of jurisprudence and international practices, provides more robust legal arguments, and supports the professionalism of law enforcement officials. Thus, the use of literature review has proven to be essential in efforts to achieve more effective, fair, and sustainable law enforcement in Indonesia.